Mandatory criteria for the application of variability-based parameters of fluid responsiveness: a prospective study in different groups of ICU patients - Huber, Wolfgang; Reindl, Wolfgang (Journal of Zhejiang University. Science B, Biomedicine & biotechnology, 2018)
Stroke volume variation (SVV) has high sensitivity and specificity in predicting fluid responsiveness. However, sinus rhythm (SR) and controlled mechanical ventilation (CV) are mandatory for their application. Several studies suggest a limited applicability of SVV in intensive care unit (ICU) patients. We hypothesized that the applicability of SVV might be different over time and within certain subgroups of ICU patients. Therefore, we analysed the prevalence of SR and CV in ICU patients during the first 24 h of PiCCO-monitoring (primary endpoint) and during the total ICU stay. We also investigated the applicability of SVV in the subgroups of patients with sepsis, cirrhosis, and acute pancreatitis.